2011
DOI: 10.1017/s0016756811000914
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentological, palynological and geochemical studies of the terrestrial Triassic–Jurassic boundary in northwestern Poland

Abstract: The Kamień Pomorski IG-1 borehole (Pomerania, NW Poland) yields a profile through the Triassic-Jurassic (T-J) transition in continental deposits. An integrated study of the sedimentology, sequence stratigraphy, palynology, biostratigraphy and geochemistry of these deposits has been carried out on the boundary interval, which represents a time of major environmental change. Two lithological units within the transitional section are distinguished: the Lower-Middle Rhaetian Wielichowo Beds of alluvial plain facie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 88 publications
(375 reference statements)
0
50
0
Order By: Relevance
“…In Gen er al ized car bon-iso tope curve and palaeoclimatic changes are mod i fied and com piled from Hesselbo et al (2002), Korte et al (2009), Ruhl et al (2009 and Pieñkowski et al (2012). Tri as sic-Ju ras sic bound ary lo ca tion is adapted from Korte et al (2009), andPieñkowski et al (2012), FAD of Psiloceras speleae and Cerebropollenites thiergartii from Hillebrandt et al (2007), and age of "ini tial" neg a tive CIE from White side et al (2010), and Ruhl et al (2010); black strip -the old est CAMP ba salt flow in the Argana Ba sin, Mo rocco (Marzoli et al, 2004;White side et al, 2010), dark grey strip -the old est CAMP ba salt flow in the New ark and Hart ford bas ins, North ern Amer ica (Olsen et al, 2002;White side et al, 2010), light grey strip -the suc ceed ing ba salt flow in the Argana Basin, Mo rocco (Marzoli et al, 2004;White side et al, 2010) Late Rhaetian-Early Hettangian times the dis tance from the near est CAMP vol ca nic erup tions to the Pol ish Ba sin did not exceed 1500 km (Pieñkowski et al, 2014). The Rhaetian was a tectoni cally quiet time, but at the be gin ning of the Hettangian there was a dis tinct fault-re lated tec tonic event (Hakenberg and OEwidrowska, 1997;Poprawa, 1997;Pieñkowski, 2004).…”
Section: Geological and Palaeogeographical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…In Gen er al ized car bon-iso tope curve and palaeoclimatic changes are mod i fied and com piled from Hesselbo et al (2002), Korte et al (2009), Ruhl et al (2009 and Pieñkowski et al (2012). Tri as sic-Ju ras sic bound ary lo ca tion is adapted from Korte et al (2009), andPieñkowski et al (2012), FAD of Psiloceras speleae and Cerebropollenites thiergartii from Hillebrandt et al (2007), and age of "ini tial" neg a tive CIE from White side et al (2010), and Ruhl et al (2010); black strip -the old est CAMP ba salt flow in the Argana Ba sin, Mo rocco (Marzoli et al, 2004;White side et al, 2010), dark grey strip -the old est CAMP ba salt flow in the New ark and Hart ford bas ins, North ern Amer ica (Olsen et al, 2002;White side et al, 2010), light grey strip -the suc ceed ing ba salt flow in the Argana Basin, Mo rocco (Marzoli et al, 2004;White side et al, 2010) Late Rhaetian-Early Hettangian times the dis tance from the near est CAMP vol ca nic erup tions to the Pol ish Ba sin did not exceed 1500 km (Pieñkowski et al, 2014). The Rhaetian was a tectoni cally quiet time, but at the be gin ning of the Hettangian there was a dis tinct fault-re lated tec tonic event (Hakenberg and OEwidrowska, 1997;Poprawa, 1997;Pieñkowski, 2004).…”
Section: Geological and Palaeogeographical Backgroundmentioning
confidence: 99%
“…More over, it was found that at mo spheric CO 2 con cen tra tions had increased ear lier in the Rhaetian (Cleve land et al, 2008;. The ear lier Rhaetian neg a tive car bon iso tope ex cursions clearly pre ceded the Late Rhaetian "ini tial" neg a tive CIE Suan et al, 2011;Lindström et al, 2012;Pieñkowski et al, 2012Pieñkowski et al, , 2014Fig. 1).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations